Implementation of social technologies and environmental education in communities of the Upper Pantanal Mato Grosso (Research, Society and Development, 2024)
This research aims to present a report of experiences with social technologies that can be replicated in rural communities in dozens of Brazilian municipalities, considering the existing capital in the various locations, as an option for solving problems related to the environment, the economic and social sectors, the production chain, and the generation of employment and income. The Social Technologies Project of INCRA and its partners sought to evaluate environmentally sustainable alternatives in the Alto Pantanal region in rural communities/settlements. From 2011 to 2023, technical visits and inspections were carried out on selected properties where sustainable social technologies were implemented: cisterns for human consumption, small dams (planting Embrapa water), multiple-use lakes (second water project), cisterns for rural schools, recovery of springs, among others. Today, 162 families of small farmers and 420 students from rural schools are supplied with water, totaling around 1,000 people in the municipalities of Cáceres, Nobres, Santo Antônio do Leverger, Várzea Grande and Chapada dos Guimarães-MT. The rainwater collected from the roofs and in the micro-basin had “zero cost”, a simple and easy-to-replicate form, and is of good quality for domestic use, educational and productive activities. The “Planting Water” project prolonged soil moisture in the micro-basin, increased the water level in the wells, and reduced erosion on rural roads. There was an improvement in family income, with the generation of new jobs in the development of production chains, such as dairy farming, and the production of native species in the region that had been facing rural exodus due to water shortages.